Corneal biomechanics: A diagnostic tool for differentiating high astigmatism and mild keratoconus - Norsyariza Razak; Wan Haslina Wan Abdul Halim; Bariah Mohd-Ali (African Vision and Eye Health)
Background: High astigmatism (HA) can be misinterpreted as keratoconus (KCN), is highly prone to developing KCN and is normally reconfirmed using corneal topography.